Efektivitas Oral Hygiene Menggunakan Povidone-Iodine 1% terhadap Pencegahan Pneumonia pada Pasien dengan Penurunan Kesadaran di Ruang ICU: The Effectiveness of Oral Hygiene Using Povidone-Iodine 1% in Preventing Pneumonia in Patients with Impaired Consciousness - Melfis Daeli; Maria Astrid (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2026)
Ventilator-Associated Pneumonia (VAP) is a nosocomial infection that frequently occurs in patients treated in the Intensive Care Unit (ICU), particularly among stroke patients with comorbid diabetes mellitus who require mechanical ventilation. Decreased level of consciousness, endotracheal tube insertion, impaired protective airway reflexes, and hyperglycemic conditions increase the risk of oropharyngeal microorganism colonization that may lead to VAP. One of the nursing interventions recommended in the VAP prevention bundle is oral hygiene using antiseptic agents. This study aimed to analyze the effectiveness of oral hygiene using 1% povidone-iodine in preventing Ventilator-Associated Pneumonia in stroke patients with diabetes mellitus receiving mechanical ventilation in the ICU. This study employed a descriptive case study design involving two patients treated in the same hospital ICU: one patient diagnosed with recurrent ischemic stroke and diabetes mellitus, and one patient diagnosed with ischemic stroke and diabetes mellitus. The nursing intervention consisted of scheduled oral hygiene using 1% povidone-iodine performed three times daily and combined with the VAP prevention bundle, including effective suctioning, 30° semi-Fowler positioning, and continuous clinical monitoring. Evaluation was conducted through clinical observation, including oral cavity hygiene, secretion characteristics, respiratory rate, oxygen saturation, random blood glucose levels, and the Modified Clinical Pulmonary Infection Score (MCPIS). The results demonstrated improved airway clearance in both patients, indicated by reduced secretion production, decreased rhonchi, stabilized respiratory rate, and increased oxygen saturation. Throughout the observation period, MCPIS values in both patients remained ≤5, and no clinical signs of VAP were identified. Therefore, oral hygiene using 1% povidone-iodine is effective in preventing Ventilator-Associated Pneumonia in stroke patients with diabetes mellitus receiving mechanical ventilation in the ICU and is recommended for integration into ICU nursing standard operating procedures.